PENGARUH MANAGERIAL OWNERSHIP DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Yuliani Almalita; Andy (E-Jurnal Akuntansi TSM, 2022)
The purposes of this study is to obtain empirical information about the effect of information audit committee, board independence, firm size, board size, audit quality, leverage, managerial ownership, financial distress on earnings management. This study uses samples from all non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2018-2020. This sampling method in this study uses the purposive sampling method. The research method uses requires criteria in taking the sample to be studied. The results of the sample found that there were 81 companies and 243 data that met the sampling criteria. This study uses multiple regression methods to perform data analysis. The results of this study indicate that the board independence has positive effect on earnings management because board independence can provide opportunities for manager to create a business strategies especially in manipulating company profits and audit quality has negative effect on earnings management because more effective audit quality in the company is able to limit the occurrence of earnings management because auditor decisions are independent decisions. In whereas, audit committee, firm size, board size, leverage, managerial ownership, and financial distress have no effect on earnings management.